1998
DOI: 10.1074/jbc.273.15.9094
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tail of the Vesicular Acetylcholine Transporter Contains a Synaptic Vesicle Targeting Signal

Abstract: The human homologue of the vesicular acetylcholine transporter (hVAChT) and the neuronal isoform of the vesicular monoamine transporter (hVMAT2) are differentially targeted to two populations of regulated secretory organelles when expressed in PC12 cells. Western blot analysis of subcellular fractions from sucrose equilibrium density gradients and glycerol velocity gradients of homogenates from stably transfected cells revealed hVAChT immunoreactivity in fractions that contain synaptophysin, a marker of synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 60 publications
7
72
1
Order By: Relevance
“…An alternative pathway for VAChT trafficking, suggested by Tao-Cheng and Eiden (54) and by Varoque and Erickson (35), utilizes the regulated secretory sorting pathway, as do VMATs, instead of the constitutive secretory pathway, Fig. 10B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative pathway for VAChT trafficking, suggested by Tao-Cheng and Eiden (54) and by Varoque and Erickson (35), utilizes the regulated secretory sorting pathway, as do VMATs, instead of the constitutive secretory pathway, Fig. 10B.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic tail of a number of membrane proteins has been shown to contain information for targeting to various intracellular destinations (32)(33)(34)(35). The VAChT cytoplasmic carboxyl tail fits into this group as it has been shown to be involved in the targeting of this transporter to synaptic vesicles (35).…”
Section: The C-terminal Cytoplasmic Tail Of Vacht Interacts With Ap Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have identified domains and motifs necessary for correct localization of SV proteins. Targeting and sorting signals have been identified in synaptophysin (Linstedt and Kelly, 1991), synaptobrevin (Grote et al, 1995;Grote and Kelly, 1996), synaptotagmin (Blagoveshchenskaya et al, 1999;Krasnov and Enikolopov, 2000), and vesicular neurotransmitter transporters (Tan et al, 1998;Varoqui and Erickson, 1998). However, no common motif that could serve as a universal targeting signal has been found by experimental studies or by direct comparison of the primary sequences of SV proteins.…”
Section: Introductionmentioning
confidence: 99%